2022
DOI: 10.1089/fpsam.2021.0107
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Instrumented Hammer for Rhinoplasty Osteotomies: A Cadaveric Study

Abstract: Question: Is it possible to determine the bone properties around the osteotome tip and the occurrence of fractures with a smart hammer during the nasal osteotomies for rhinoplasties? Findings: A predictive algorithm was developed to detect the occurrence of fractures, and the close proximity of the osteotome to the frontal bone.Meaning: Rhinoplasty surgeons may value the ability to have instant feedback while performing nasal osteotomies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, cracks may appear during rhinoplasty [ 35 ]. We have shown in previous studies corresponding to rhinoplasty [ 27 , 28 , 29 ] that this crack in front of the osteotome tip can be detected by a sudden decrease in the value of τ due to a decrease of the sample rigidity. Therefore, further work is needed to distinguish situations where a decrease in τ is due to (i) the osteotome reaching the end of the sample and (ii) the creation of a crack around the osteotome tip.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, cracks may appear during rhinoplasty [ 35 ]. We have shown in previous studies corresponding to rhinoplasty [ 27 , 28 , 29 ] that this crack in front of the osteotome tip can be detected by a sudden decrease in the value of τ due to a decrease of the sample rigidity. Therefore, further work is needed to distinguish situations where a decrease in τ is due to (i) the osteotome reaching the end of the sample and (ii) the creation of a crack around the osteotome tip.…”
Section: Discussionmentioning
confidence: 94%
“…Later, it was also shown that the instrumented hammer could be used to detect a change in the tissue material properties during a rhinoplasty performed in rabbits [ 27 ] using a machine learning algorithm. The method was eventually applied to an anatomical subject showing the feasibility of this approach in a configuration close to that of the operating room [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%